The Impact of Product Quality and Brand on Purchase Decision: A Study on Elzatta Hijab Products in Sidoarjo: Pengaruh Kualitas Produk dan Merek Terhadap Keputusan Pembelian: Studi pada Produk Hijab Elzatta di Sidoarjo - Weni Apriliyah; Mudji Astuti (Academia Open, 2024)
This quantitative research aims to investigate the influence of product quality and brand on purchase decisions for Elzatta Hijab products in Sidoarjo. Using purposive sampling, 100 respondents who had purchased Elzatta Hijab products in Sidoarjo were surveyed. The study employed validity and reliability tests for data quality assessment and conducted multiple linear regression analysis using SPSS version 18.0 for data analysis. The findings reveal that both product quality and brand have a significant individual impact on purchase decisions. Furthermore, when considered simultaneously, product quality and brand collectively exert a significant influence on purchase decisions. These results underscore the importance of product quality and brand perception in shaping consumer purchase choices, offering valuable insights for marketers and businesses in the hijab industry. Highlights: Product Quality and Brand Influence: This study demonstrates the significant impact of product quality and brand on consumer purchase decisions, emphasizing their crucial role in the marketplace. Consumer Preferences: The research highlights the importance of understanding consumer preferences in the hijab industry, particularly in Sidoarjo, providing valuable insights for businesses. Marketing Strategy Insights: The findings offer practical insights for marketers to formulate effective strategies for promoting hijab products and enhancing brand perception. Keywords: Product Quality, Brand, Purchase Decision, Elzatta Hijab, Consumer Behavior